Pengendalian Kualitas Produksi Kemasan Flexible X Menggunakan Metode Failure Mode and Effect Analysis (FMEA) untuk Mereduksi Defect di PT XYZ - Farah Miftahul Aulia; Iqbal Yamin; Wiwi Prastiwinarti (Jurnal Rekayasa Sistem Industri, 2026)
Flexible packaging product X manufactured by PT XYZ—a flexible packaging company employing rotogravure printing technologym recorded a defect rate of 4.57% during the production period from September to November 2023, exceeding the company’s tolerance limit of 4%. This study aims to identify the dominant defect types, analyze their root causes, and formulate improvement recommendations using the Failure Mode and Effect Analysis (FMEA) approach. The method evaluates potential risks through the parameters of Severity, Occurrence, and Detection, and determines the Risk Priority Number (RPN) as the basis for prioritizing corrective actions.The Pareto analysis revealed three dominant defect types: missprint (37%), blocking (24.9%), and blushing (20.3%). The highest RPN value was found in missprint (810), attributed to uneven film surface (film flatness), followed by blocking (648) due to improper film tension, and blushing (648) resulting from excessive ink viscosity. Based on these findings, technical improvement proposals were developed, including tighter raw material quality control, adjustment of drying temperature and film tension parameters, and stricter ink viscosity inspection procedures.The novelty of this research lies in the integration of Statistical Process Control (SPC) and FMEA in analyzing defect risks in the rotogravure printing process. This integration enables the formulation of data-driven and process-parameter-oriented improvement recommendations, bridging the gap between qualitative risk assessment and practical quality control implementation in the flexible packaging industry. The proposed improvements are expected to minimize process variation, reduce defect recurrence, and enhance the overall capability of the rotogravure printing process at PT XYZ.